Treatment of patients with newly diagnosed metastatic hormone sensitive prostate cancer (mHSPC) in Belgium: a real world data analysis. Issue 6 (2nd November 2022) - Lambert, E; Hollebosch, S; van Praet, C; Van Bruwaene, S; Duck, L; De Roock, W; van Wambeke, S; Ghysel, C; Ameye, F; Schatteman, P; Vandenbroucke, F; Sautois, B; et al.
ABSTRACT: INTRODUCTION: Abiraterone acetate + prednisone (AAP) and docetaxel have proven their efficacy in the treatment of patients with newly diagnosed metastatic hormone-sensitive prostate cancer (mHSPC) in clinical trials. However, real-world data are scarce. The goal of this study is to evaluate real-world data on the efficacy and safety of these therapies in mHSPC patients. PATIENTS AND METHODS: Records of 93 patients from 21 different centres were retrospectively reviewed. Primary and secondary endpoints were radiographic and PSA progression-free survival (RPFS – PSA-PFS) and cancer specific and overall survival (CSS – OS), respectively. Adverse events (AEs) were evaluated according to the Common Terminology Criteria for Adverse Events version 5.0. Differences in oncological outcome and AEs were evaluated between three treatment groups: ADT only (N=26) – ADT + AAP (N=48) – ADT + docetaxel (N=19). Survival analysis was performed using Kaplan–Meier statistics. RESULTS: Median RPFS was 13 months (95% confidence interval [CI]: 9–17) for ADT only, 21 months (95% CI: 19–23) for ADT + AAP and 12 months (95% CI: 11–14) for ADT + docetaxel (p = 0.004). The 1-year PSA-PFS, CSS and OS were 73.5%, 90.7% and 88.7%, respectively, with no significant differences between the three groups. Adverse events of grade 3 or higher were not observed more frequently. CONCLUSION: Retrospective real-world data show a significantly longer RPFS for mHSPC patients treated with ADT + AAP compared to ADT only or ADT + docetaxel at short-term follow-up. This can aid in counselling of mHSPC patients in daily clinical practice.